KEEFEKTIFAN KONSELING KELOMPOK SFBC MENINGKATKAN SELF EFFICACY SISWA SMP NEGERI 19 PONTIANAK - Summiyati, Mahza; Asrori, Muhammad; Putri, Amallia (Academy of Education Journal, 2023)
The primary objective of this study is to examine the efficiency of Solution Focused Brief therapy (SFBC) group therapy as a means of enhancing the self-efficacy levels among seventh-grade students at SMP N 19 Pontianak. The chosen research methodology was experimentation, specifically employing a pre-experimental design research approach with a pre-test-post-test one group design. The participants in this study were selected using a purposive sampling technique. Specifically, a sample of 10 individuals with poor self-efficacy was drawn from a population of 31 individuals. Based on the computed data, the mean score of the pre-test (before to receiving any intervention) was 96 within the low category, while the post-test (after the administration of treatment) had an average score of 136 within the high group. The T statistic was derived using the Paired sample T-test, yielding a result of -3.928, accompanied by a significance level (Sig value). The p-value of 0.03, calculated using a two-tailed test, is less than the significance level of 0.05. This indicates that the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. Therefore, there is a significant difference in student self-efficacy before and after receiving SFBC group counseling treatment. Based on the findings, it can be inferred that SFBC group counseling demonstrates efficacy in enhancing the self-efficacy levels of seventh-grade students enrolled at SMP N 19 Pontianak.